PENGARUH TEKNIK COGNITIVE RESTRUCTURING TERHADAP KECEMASAN SOSIAL SISWA - Muhammad Rifaldi; M. Syarafuddin; I Made Sonny Gunawan (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2020)
The purpose of this study was to determine the effect of cognitive restructuring techniques on students' social anxiety. The research design used in this study was one group pretest-posttest design.The population in this study was grade VII students of SMPN 5 Gerung with a total of 37 students, and the samples in this study were 9 people who were indicated to have high levels of social anxiety based on the results pre-test. The sampling technique used was purposive sampling. Data collection techniques used were questionnaires as the main method and methods of observation, interviews and documentation as a complementary method. The results of this study indicate that cognitive restructuring techniques have an effect on minimizing students' social anxiety.